Avian influenza outbreaks in domestic cats: another reason to consider slaughter-free cell-cultured poultry? - Rzymski, Piotr (Frontiers in Microbiology, 2023)
Avian influenza causes substantial economic loss in the poultry industry and potentially threatens human health. Over recent years, the highly pathogenic avian influenza A/H5N1 virus has led to devastating losses in poultry flocks and wild birds. At the same time, the number of mammalian species identified to be infected with A/H5N1 is increasing, with recent outbreaks in domestic cats, including household individuals, evidenced in July 2023 in Poland, ultimately creating opportunities for the virus to adapt better to mammalian hosts, including humans. Overall, between 2003 and 2023, over ten outbreaks in felids have been documented globally, and in six of them, feed based on raw chicken was suspected as a potential source of A/H5N1, fuelling a debate on threats posed by A/H5N1 and methods to decrease the associated risks. This article debates that technology allowing the production of slaughter-free meat, including poultry, from cell and tissue cultures could be considered as a part of a mitigation strategy to decrease the overall burden and threat of adaptation of avian influenza viruses to human hosts. By shifting poultry production to the cultured meat industry, the frequency of A/H5N1 outbreaks in farmed birds may be decreased, leading to a reduced risk of virus acquisition by wild and domesticated mammals that have direct contact with birds or eat raw poultry and have close contact with human (including domestic cats), ultimately minimizing the potential of A/H5N1 to adapt better to mammalian host, including humans. This adds to the list of other benefits of cultured meat that are also reviewed in this paper, including decreased antibiotic use, risk of microbial contamination and parasite transmission, and environmental and ethical advantages over conventional slaughtered meat. In conclusion, further development and implementation of this technology, also in the context of poultry production, is strongly advocated. Although cultured poultry is unlikely to replace the conventional process in the near future due to challenges with scaling up the production and meeting the continuously increased demand for poultry meat, it may still decrease the pressures and threats related to the transmission of highly pathogenic avian influenza in selected world regions.